Perlindungan Hukum Pemegang Saham Minoritas Perseroan Terbatas Tertutup dan Keadilan Berdasar Pancasila - Mustaqim Mustaqim; Agus Satory (Faculty of Law, Universitas Pattimura, 2019)
Legal protection for the majority shareholders is sufficiently guaranteed, especially through the mechanism of the RUPS, but this is not the case for minority shareholders, thus creating an injustice problem for minority shareholders. The purpose of this study is to uncover and find out legal protection for minority shareholders in a limited liability company based on Pancasila justice. This research is normative juridical so it uses secondary data with the law approach and qualitative data analysis. The results showed that the General Meeting of Shareholders did not reflect legal protection for minority shareholders, because in every decision making through the General Meeting of Shareholders and various other decisions based on the attendance quorum about the majority of votes present at the General Meeting of Shareholders. Such matter is detrimental to the interests of minority shareholders because without the presence of minority shareholders, a General Meeting of Shareholders can be held, while minority shareholders also have the same rights and obligations and responsibilities. The majority of shareholders hold a large and full control over the company, resulting in minority shareholders, there is no guarantee to get justice based on Pancasila justice. Therefore, the General Meeting of Shareholders must be held if attended by all shareholders with voting rights present or represented. If this is not the case, the results of the General Meeting of Shareholders may be canceled.